Early indicators of change: divergent climate envelopes between tree life stages imply range shifts in the western United States. Issue 2 (13th October 2013) - Bell, David M.; Bradford, John B.; Lauenroth, William K.
Abstract Aim To determine if differences in climate envelopes for six coniferous tree species and two life stages (trees and seedlings) suggest a potential for species range contractions, expansions or shifts in response to climate change and if these patterns differ between subalpine (i.e. cool‐climate) and montane (i.e. warm‐climate) species. Location The dry domain of the western United States. Methods Using data from the Forest Inventory and Analysis National Program, we quantified the relationship between probability of occurrence and climate for adults and seedlings of each species with a Bayesian logistic regression. Assuming that distributional differences between life stages highlight shifting regeneration patterns relative to adult trees, we assessed differences between seedlings and adult trees based on predicted probabilities of occurrence and climate envelope boundaries. Results Differences between occurrence probabilities for seedlings and adults were greatest for montane, as opposed to subalpine, species and along range margins, especially in the southern and western portions of the study area. Climate envelope boundaries of seedlings differed from adult trees most frequently in montane species and often suggested range contractions or range shifts, as opposed to range expansion. Main conclusions Our results indicated that climate‐induced contractions and shifts in seedling distribution in response to recent change are already under way and are particularly severe in montane tree species. While adult trees may persist for hundreds of years without significant regeneration, tree species ranges will eventually contract where tree regeneration fails.